Longitudinal association between maternal response to child emotion and child regulation of anger and worry - Schmechel, Lindey Kaye (Kansas State University, 2023)
The importance of children’s emotion regulation skills has been well documented. The healthy management of emotion in children is related to numerous positive outcomes—both short-term and long-term—such as reacting better to stress, preventing and handling various problems, and effectively engaging in peer relationships. Conversely, poor emotion-related skills have been linked with a myriad of negative outcomes, such as poor social competence, and have been linked to externalizing and internalizing behaviors, and been identified as a transdiagnostic risk factor in the development of various psychopathological disorders. Parenting has been shown to have a powerful influence on the development of children’s healthy emotion management. Children learn about emotions and the skills related to them through both explicit (e.g., overt discussions) and implicit (e.g., observations of parent’s behaviors) means. Since parents play such a crucial role in how children learn about emotions and the strategies they use to manage them, it is important that we examine the behaviors parents engage in in response to various child emotions and how those responses are related to child management of different emotions. This study explored the longitudinal association between maternal response to child emotion and child regulation of anger and worry. The sample consisted of 112 children and 112 mothers at two different time points (Wave 1 = 1st grade, Wave 5 = 4th grade). All data came from the Families and School for Health (FiSH) dataset. A correlation was conducted followed by two multiple regressions. Mother punitive reactions at Wave 1 was found to be significantly correlated with overall child report of anger at Wave 5. Mother minimization reactions at Wave 1 was found to be significantly correlated with overall child report of worry. Overall Child Report of Anger at Wave 5 was correlated significantly with Overall Child Report of Worry at Wave 5. Mother’s punitive, minimization, and distressed reactions were likewise found to significantly correlate with one another. When including the three non-supportive maternal responses and the control variables, only punitive reactions in Wave 1 was found to be significantly associated with increased child dysregulation of anger at Wave 5. When including the three non-supportive maternal responses and the control variables, only mothers’ minimization reactions in Wave 1 was found to be related to increased child dysregulation of worry at Wave 5.
Keywords: Emotion regulation; Parental response; Maternal response; Emotion regulation skills; Non-supportive responses; Parent socialization of emotion